Retakaful - Abd Haris, Fatin Nadirah; Abdul Latif, Nor Hakimah; Bahar, Nursyazwana; Mohd Saad, Siti Nurfatihah (2025)
Retakaful, also known as Islamic reinsurance, is a critical component of the Islamic financial system and plays a vital role in supporting the operations of takaful (Islamic insurance) companies. As with conventional insurance, takaful operators must manage their exposure to high levels of risk by spreading it across other entities. However, because conventional reinsurance contracts often involve elements that contravene Shariah principles such as interest (riba), excessive uncertainty (gharar), and gambling (maysir) they are not suitable for Islamic financial institutions. This has led to the development of retakaful as a Shariah-compliant alternative. Retakaful operates on Islamic contractual models such as wakalah (agency) and mudarabah (profit-sharing), which emphasize risk-sharing, mutual cooperation (ta’awun), and ethical investment of funds. In a typical retakaful arrangement, participating takaful operators contribute to a common retakaful fund that is used to indemnify members who suffer losses, in accordance with Shariah guidelines. The retakaful operator manages the fund and may receive a fee (in wakalah models) or share in the investment profit (in mudarabah models), depending on the agreed terms. The core objective of retakaful is to protect takaful operators from unforeseen losses while maintaining Shariah compliance in all financial and operational aspects. It ensures the sustainability and solvency of takaful institutions by providing a safety net for large-scale risks that individual operators may not be able to bear alone. Moreover, it promotes the development of the global Islamic finance ecosystem by offering a halal (permissible) alternative toconventional risk transfer mechanisms. As Archer, Abdel Karim, and Nienhaus (2009) highlight, the growth and effectiveness of the takaful industry are closely linked to the availability of robust retakaful solutions. Without an effective retakaful sector, takaful operators may be forced to rely on conventional reinsurance, which compromises the integrity and religious permissibility of their operations. Therefore, developing strong, competitive, and globally recognized retakaful institutions is crucial for the continued advancement of Islamic finance.